The effect of improved fodder production on livestock productivity in Endamehoni District, southern Tigray Ethiopia - Hailesilassie, H. (Mekelle University, 2016)
Feed shortage and low quality of available feeds are constraints for livestock production in the highlands of Ethiopia. Improved fodder production combined with appropriate postharvest handling practices have been practiced to alleviate the problems. The objective of this study was to evaluate the perception of farmers on improved fodder and quantify the effects of improved fodder in livestock performance, forage yield and quality of intercropped oat-vetch and benefits obtained from the fodder production. The study involved both field observation and questionnaire with 40 purposively selected livestock owners who practiced improved fodder production. The effect of cultivated oat-vetch supplementation on daily body weight gain and milk yield was quantified using 8 oxen, 7 cows and 3 sheep. Forage biomass yield on dry matter (DM) basis was calculated after drying a sample of 300g green forage in an oven at 600c for 48 hours .data analysis for Statistical analysis system (SAS) was used to carry out descriptive statistics on questionnaire data and field observation variables. Feed shortage has been a major constraint for animal production during dry periods and farmers use different coping mechanisms ranging from purchasing of feeds from the market and destocking unproductive animals. The majority of the interviewed households practice irrigation and produce cultivated fodders such as oat-vetch, alfalfa, phalaris and elephant grass. The oat-vetch mixture DM yield in Embahasti (8.71 t/ha) was significantly higher than that in Tsibet (6.48 t/ha), (P<0.05). The mean DM, Ash, OM, CP, NDF, ADF and ADL content of oat-vetch mixture were 94.4, 8.9, 91.1, 11.9, 65.9, 45.9 and 6.1, respectively. The TIVOMD (%) and ME (MJ/kg DM) of oat-vetch mixture were also 60.2 and 8.85, respectively. All respondent farmers replied that supplementation of cultivated fodders to their animals have resulted in positive impact on milk yield, body weight gain, health and coat color of their animals. On-farm observation of the performance of animals indicated that supplemented cows, oxen and sheep were able to gain 293, 265 and 88.9 g of weight per day respectively,. The average daily gain of crossbreed cattle and local cattle breed were 161 and 307g, respectively. Moreover, the oat-vetch supplementation resulted in daily additional milk yield of 2.33 liters per cow for crossbreed cattle, and 1.0 liters per cow for local cattle. Development of fodder plants, such as herbaceous forage legumes and fodder trees species in their farm land can mitigate the constraints of feed scarcity and improves livestock productivity. The study recommends the development of fodder plants, such as herbaceous forage legumes and fodder trees species in their farm land which can mitigate the constraints of feed scarcity and their expensive price.